Nitrospina-Like Bacteria Are Potential Mercury Methylators in the Mesopelagic Zone in the East China Sea - Tada, Yuya; Marumoto, Kohji; Takeuchi, Akinori (Frontiers in Microbiology, 2020)
In natural environments, production of neurotoxic and bioaccumulative methylmercury (MeHg) is mediated by microorganisms carrying genes hgcA and hgcB. However, the contribution of these microorganisms to mercury (Hg) methylation or MeHg accumulation in the ocean is poorly understood. Here, we determined total Hg and MeHg concentrations in seawater samples and conducted a metagenomic survey of the hgcAB genes and functional modules involved in metabolic pathways in the East China Sea (ECS). In the metagenomic analyses, we used paired-end reads and assembled contigs for hgcAB enumeration and phylogenetic analyses in the seawater column. To evaluate the relative abundance of hgcAB in the metagenomic data, we estimated the abundance of recA (single-copy gene of bacteria) as well and then compared them. Moreover, profiles of prokaryotic community composition were analyzed by 16S rRNA gene (V4 region) deep-sequencing. In the mesopelagic layers, hgcA sequences were detected, and there was a positive correlation between hgcA abundance relative to recA and MeHg concentrations. Thus, the quantification of the hgcA sequences could provide valuable information to evaluate potential environments of microbial MeHg accumulation in the seawater column. Phylogenetic analysis using the assembled contigs revealed that all of hgcA sequences in the mesopelagic layers were affiliated with Nitrospina-like sequences. The 16S rRNA gene analysis revealed that Nitrospinae were abundant in the mesopelagic layers. Although the lineages of Deltaproteobacteria, Firmicutes, and Spirochaetes were detected in the seawater column, their hgcAB sequences were not detected in our metagenomes, despite the fact that they are closely related to previously identified Hg methylators. Metabolic pathway analysis revealed that modules related to sulfur and methane metabolism were prominent in the mesopelagic layers. However, no hgcA sequences affiliated with sulfate-reducing bacteria or methanogens were detected in these layers, suggesting that these bacteria could not be strongly involved in Hg accumulation in the seawater column. Our results indicate that Nitrospina-like bacteria with hgcAB genes could play a critical role in microbial Hg accumulation in the oxygenated mesopelagic layers of the ECS.